2017
DOI: 10.1136/bmjopen-2017-016833
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hospital volume on nephrectomy mortality and complications: a systematic review and meta-analysis stratified by surgical type

Abstract: ObjectivesThe provision of complex surgery is increasingly centralised to high-volume (HV) specialist hospitals. Evidence to support nephrectomy centralisation however has been inconsistent. We conducted a systematic review and meta-analysis to determine the association between hospital case volumes and perioperative outcomes in radical nephrectomy, partial nephrectomy and nephrectomy with venous thrombectomy.MethodsMedline, Embase and the Cochrane Library were searched for relevant studies published between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 60 publications
1
38
0
2
Order By: Relevance
“…When it comes to nephrectomy, there is also a need to account for different nephrectomy types (RN vs PN vs CN) considering the differences in technical complexity and rates of adverse outcomes. One recent systemic review with stratified meta‐analyses included 16 studies, the majority of which focused on RN (10 studies on RN, two studies on nephrectomy with thrombectomy, and four studies on PN) . Our study adds to the literature with novel findings showing the volume‐outcome association in the setting of CN.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…When it comes to nephrectomy, there is also a need to account for different nephrectomy types (RN vs PN vs CN) considering the differences in technical complexity and rates of adverse outcomes. One recent systemic review with stratified meta‐analyses included 16 studies, the majority of which focused on RN (10 studies on RN, two studies on nephrectomy with thrombectomy, and four studies on PN) . Our study adds to the literature with novel findings showing the volume‐outcome association in the setting of CN.…”
Section: Discussionmentioning
confidence: 85%
“…In the field of urology, numerous studies focused on radical cystectomy and radical prostatectomy . However, there is a paucity of data on the association between surgical volume and outcomes after nephrectomy . When it comes to nephrectomy, there is also a need to account for different nephrectomy types (RN vs PN vs CN) considering the differences in technical complexity and rates of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital volume and surgeon volume were independent predictors of perioperative outcomes of patients undergoing RAPN, with hospital volume playing a greater impact than surgeon volume . A systematic review and meta‐analysis confirmed improved outcomes in the UK following the centralization of care …”
mentioning
confidence: 87%